Development of a Tablet-Based Participation Measure for Older Adults in Outpatient Rehabilitation Settings...2020 AOTA Annual Conference & Expo - Chang, Feng-Hang; Su, Yu; Tseng, Zong-Liang (American Journal of Occupational Therapy)
Date Presented 03/28/20 We developed a tablet-based participation measure and compared its reliability, concordance, and acceptability to older adults in outpatient rehabilitation settings with the paper-form version. Findings of this study provide supportive evidence for administering a tablet-based participation measure to older populations in rehabilitation settings and suggest a promising measurement methodology for future OT practice. Primary Author and Speaker: Feng-Hang Chang Contributing Authors: Yu Su, Zong-Liang Tseng